AUNX1, a novel locus responsible for X linked recessive auditory and peripheral neuropathy, maps to Xq23–27.3. Issue 7 (30th June 2006) - Wang, Q J; Li, Q Z; Rao, S Q; Lee, K; Huang, X S; Yang, W Y; Zhai, S Q; Guo, W W; Guo, Y F; Yu, N; Zhao, Y L; Yuan, H; et al.
Abstract : Background: We report here the genetic characterisation of a large five generation Chinese family with the phenotypic features of auditory neuropathy and progressive peripheral sensory neuropathy, and the genetic feature of X linked recessive inheritance. Disease onset was at adolescence (at an average age of 13 years for six affected subjects). The degree of hearing impairment varied from mild to severe, with decreased otoacoustic emissions; auditory brainstem responses were lacking from onset. Methods: Two-point and multipoint model based linkage analysis using the MILNK and LINKMAP programs of the FASTLINK software package produced maximum two-point and multipoint LOD scores of 2.41 and 2.41, respectively. Results: These findings define a novel X linked auditory neuropathy locus/region ( AUNX1, Xq23–q27.3). This region is 42.09 cM long and contains a 28.07 Mb region with flanking markers DXS1220 and DXS8084, according to the Rutgers Combined Linkage-Physical Map, build 35. However, mutation screen of the candidate gene SLC6A14 within the region did not identify the causative genetic determinant for this large Chinese family.